(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This scientific article presents the analysis of the marketing activities of the enterprises operating in our country and the factors of formation of the marketing strategy. The purpose of writing this article is to provide representatives of this field and future entrepreneurs with an understanding of the analysis of the marketing activity of enterprises and the factors of forming a marketing strategy. Result: development of effective aspects of marketing strategy in the mind of young generation and entrepreneurs.